ANALISIS TINDAKAN AKTOR-AKTOR POLITIK JELANG PEMILU TAHUN 2024 DALAM PROSES PENCALONAN MELALUI MEDIA SOSIAL - Reza Retamara; Kun Budianto; Reni Apriani (Jurnal Prodi Ilmu Politik, 2023)
ABSTRACT This study discusses the Political Dynamics of the Presidential nomination process in the 2024 election through social media.. This study aims to find out how the political dynamics are in the presidential nomination process in the 2024 election. The objects in this study are politicalactors who have been busy talking about participating in the Presidential election in 2024 these actorsare Ganjar Pranowo, Prabowo Subinato, Anies Baswedan, Sandiaga Uno, Agus Yudhoyono, Erick Thohir, Airlangga Hartarto and Puan Maharani. The theory used in this research is the theory of Political Actor Action because this theory can analyze actions and actions that occur in political dynamics in the process of nominating the President in the 2024 election through social media. This type of research is exploratory and qualitative approach. The data in this study is by analyzing social media posts for every action or action of political actors and political parties in the presidential nomination process.The results of the study show that the political dynamics in the process of nominating the President for the 2024 election is caused by indicators of actions and actions to achieve the desired goals ahead of the upcoming elections. First, political dynamics in the context of political parties and second, political dynamics in the context of figures of political actors.